Cultural sensitivity and barriers: Sami people with disabilities facing the welfare system - Melbøe, Line (Community Development Journal, 2018)
This is a pre-copyedited, author-produced version of an article accepted for publication in Community Development Journal Community Development Journal, 53 (3), 537-555, is available online at: https://doi.org/10.1093/cdj/bsy025 . The aim of this article is to increase the understanding of the participation barriers Sami people with disabilities experience in encounters with the Norwegian welfare system. According to the Sami Act of 1987, § 3–5, the Sami in Norway have a legal right to receive equitable health and social services adapted to the Sami language and culture. The focus of this article is the experiences of disabled Sami citizens in encounters with welfare services. Cultural differences and a historically recent and draconian assimilation process seem to influence Sami people’s experiences. According to our informants, mainstream society’s limited cultural competence has a negative impact on these encounters. The welfare system offers standardized services adapted to the majority in society, involving the homogenization of an impairment, where disabled people are treated the same regardless of their cultural background. This does not lead to equitable services because services are not adapted to Sami thinking, values, attitudes, or life philosophy of life. Due to the lack of cultural sensitivity, Sami people with disabilities risk experiencing double discrimination in Norwegian welfare services, experiencing barriers to participation related to both their disability and their ethnicity. This makes an intersectionality perspective relevant, treating oppression and subordination as due to the combined effects of being Sami and having an impairment. Our study indicates that the lack of knowledge about Sami culture, language, and identity among Norwegian service providers leads to an oppressive practice and results in participation barriers to Sami people with disabilities.